2020
DOI: 10.1016/j.jgo.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 risk contagion: Organization and procedures in a South Italy geriatric oncology ward

Abstract: The novel coronavirus disease Sars-Cov-2 (COVID-19) has rapidly spread through the world, since the first cases were registered in the Hubei province of China in December 2019. Its disparate clinical conditions can lead to a severe bilateral interstitial pneumonia, and thus demand intensive care beds, overwhelming the healthcare system in every Nation. The World Health Organization declared the pandemic on March 11, 2020, when the disease spread globally, with Italy being the first nation severely affected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…They documented several procedures that could help in preventing disease transmission among patients. These procedures encompassed the use of a telephone triage before admission, and the application of telemedicine [12]. In CG, appointments and triage protocols were to be performed virtually through telemedicine such as mobile phones, applications or the websites, thereby, clinical visits were to be performed based on reserved numbers and recommended time.…”
Section: Discussionmentioning
confidence: 99%
“…They documented several procedures that could help in preventing disease transmission among patients. These procedures encompassed the use of a telephone triage before admission, and the application of telemedicine [12]. In CG, appointments and triage protocols were to be performed virtually through telemedicine such as mobile phones, applications or the websites, thereby, clinical visits were to be performed based on reserved numbers and recommended time.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures encompassed the use of a telephone triage before admission, and the application of telemedicine [12]. In CG, appointments and triage protocols were to be performed virtually through telemedicine such as mobile phones, applications or the websites, thereby, clinical visits were to be performed based on reserved numbers and recommended time.…”
Section: Discussionmentioning
confidence: 99%
“…Gambardella et al reported their experience regarding treatment for old cancer patients. They documented several procedures that could help in preventing disease transmission among patients [12]. These procedures encompassed the adoption of a preadmission telephone triage, and the implementation of telemedicine.…”
Section: Discussionmentioning
confidence: 99%